2019
DOI: 10.1177/1362361319894824
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of teacher ratings on the Adapted Skillstreaming Checklist for children with autism spectrum disorder

Abstract: This study assessed the reliability and criterion-related validity of teacher ratings on the Adapted Skillstreaming Checklist for a sample of 133 children, aged 6–11 years, with autism spectrum disorder (without intellectual disability). Internal consistency for the total sample was 0.93. For a subsample, test–retest reliability was very good ( r = 0.74; intraclass correlation coefficient = 0.85) at a 9-month interval. Child age, intelligence quotient, language abilities, and sex were not associated with the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…They found that some of the observation instrument scores were psychometrically sound (i.e., favorable interrater reliability), but they caution their continued use because the scales may no longer be aligned to current conceptions of giftedness. Additionally, several other studies have also illustrated adequate validity and reliability of teacher ratings using different types of observation scales (see Hunter et al, 2018;Kettler & Albers, 2013;Lopata et al, 2020;Nordness et al, 2019;Reid et al, 2014;Smith et al, 2018). Further, to identify students for gifted services and to ensure the scores on the measures are reflective of studentobserved behaviors, teachers need to be provided adequate and appropriate training to use the scales (Renzulli et al, 2013;S ¸ahin & Çetinkaya, 2015;Styck et al, 2021;Szymanski & Shaff, 2013).…”
Section: Variability In Teacher Ratings Of Student Abilitiesmentioning
confidence: 99%
“…They found that some of the observation instrument scores were psychometrically sound (i.e., favorable interrater reliability), but they caution their continued use because the scales may no longer be aligned to current conceptions of giftedness. Additionally, several other studies have also illustrated adequate validity and reliability of teacher ratings using different types of observation scales (see Hunter et al, 2018;Kettler & Albers, 2013;Lopata et al, 2020;Nordness et al, 2019;Reid et al, 2014;Smith et al, 2018). Further, to identify students for gifted services and to ensure the scores on the measures are reflective of studentobserved behaviors, teachers need to be provided adequate and appropriate training to use the scales (Renzulli et al, 2013;S ¸ahin & Çetinkaya, 2015;Styck et al, 2021;Szymanski & Shaff, 2013).…”
Section: Variability In Teacher Ratings Of Student Abilitiesmentioning
confidence: 99%